Glycine max and Glycine soja are capable of cold acclimation. (19th June 2017) - Robison, J.; Arora, N.; Yamasaki, Y.; Saito, M.; Boone, J.; Blacklock, B.; Randall, S.
Abstract: Soybean has been considered a cold intolerant species; based largely upon seed germination and soil emergent evaluations. This study reports a distinct acquisition of cold tolerance, in seedlings, following short acclimation periods. Diversity in cold responses was assessed in eight cultivars of Glycine max and six accessions of G. soja . All varieties of soybean significantly increased in freezing tolerance following acclimation. This study indicates soybean seedlings are indeed capable of sensing cold and acquiring cold tolerance. Germination rates after cold imbibition were negatively correlated with maturity group, but positively correlated with cold acclimation potential in G. soja . Seed fatty acid composition was varied between the species, with Glycine soja accessions containing about 2‐times more linolenic acid (18:3) than G. max . Furthermore, high levels of linoleic acid (18:2) in seeds were positively correlated with germination rates following cold imbibition in G. soja only. We suggest that domestication has not impacted the overall ability of soybean to cold acclimate at the seedling stage and that there is little variation within the domesticated species for ability to cold acclimate. Thus, this brief comparative study reduces the enthusiasm for the "wild" species as an additional source of genetic diversity for cold tolerance.